My Beautiful Laundrette: Hybrid “Identity”, or the Paradox of Conflicting Identifications in “Third Space” Asian-British Cinema of the 1980s - Calvo Pascual, Mónica (Miscelánea: A Journal of English and American Studies, 2002)
This essay will attempt to define Kureishi and Frears’ 1985 film as a mid-1980s British-Asian film that escapes the “burden of representation” that characterised earlier Black British cinema in two main ways. Firstly, through the representation of the British-Asian protagonist as a homosexual with a “Thatcherite” entrepreneurial drive, the film subverts the notion of the Black community as the homogeneous entity which the “cinema of duty” set out to portray. And then, the film’s generic and technical hybridity breaks with the “realism” of those earlier films and, through its representation of “reality” as fragmentary, relative and contradictory, creates a space for the questioning of received notions of “identity”. Thus, the British-Asian protagonist is represented in his individualistic struggle as reconstructing his sense of “identity” out of the traces he finds most convenient from each of the different cultures that inform his ethnic hybridity, a process that is revealed as being essentially paradoxical.
Keywords: Ethnic hybridity; Third space; New realism; In-betweenness